Report on Evaluation of the High Yielding Varieties Programme Kharif—1968 - Planning Commission (Planning Commission, 1969)
With the introduction of high yielding varieties of cereal crops from 1966-67, the prospects of a breakthrough in agriculture brightened up. Because of the importance of this programme to our agricultural economy, the P.E.O. initiated a detailed evaluation study on a continuing basis from 1967-Kharif season at the instance of the Planning Commission. This report is based on the field enquiry conducted during kharif-68 covering 44 development blocks in as many districts, a sample of 974 participant cultivators and 643 non-participants for the four relevant kharif crops, viz. paddy, jowar, bajra and maize.
Programme Evaluation Organisation Planning Commission Government of India
Programme Evaluation Organisation Planning Commission Government of India